2014
DOI: 10.1186/scrt492
|View full text |Cite
|
Sign up to set email alerts
|

TNFα and IL-1β influence the differentiation and migration of murine MSCs independently of the NF-κB pathway

Abstract: IntroductionMesenchymal stem cells (MSCs) have the ability to repair and regenerate tissue, home to sites of inflammation, and evade the host immune system. As such, they represent an attractive therapy for the treatment of autoimmune inflammatory diseases. However, results from in vivo murine studies in inflammatory arthritis have been conflicting, and this may be due to the genetic background of the MSCs used. It is known that the inflammatory milieu may influence properties of MSCs and that, in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 63 publications
4
42
0
Order By: Relevance
“…On the other hand, Lacey et al have shown that osteogenic differentiation from the MSCs population is suppressed by pro-inflammatory cytokines (IL-1 and TNF-a) [42]. Sullivan et al demonstrated the same results as well as suppression of adipogenic differentiation by proinflammatory cytokines [43]. Related to effect of IL-6 on MSCs behavior, Pricola et al have shown that IL-6 inhibits adipogenic and chondrogenic differentiation of MSCs and maintains MSCs in undifferentiated state [44].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, Lacey et al have shown that osteogenic differentiation from the MSCs population is suppressed by pro-inflammatory cytokines (IL-1 and TNF-a) [42]. Sullivan et al demonstrated the same results as well as suppression of adipogenic differentiation by proinflammatory cytokines [43]. Related to effect of IL-6 on MSCs behavior, Pricola et al have shown that IL-6 inhibits adipogenic and chondrogenic differentiation of MSCs and maintains MSCs in undifferentiated state [44].…”
Section: Discussionmentioning
confidence: 93%
“…The fracture hematoma is a rich medium abundant in inflammatory molecules, including IL-1b, IL-6, IL-8, IL-10, HMGB1, and TNF-a, which regulate the inflammatory response and initiate chemotaxis and cell proliferation and differentiation (8,(35)(36)(37). Many reports have investigated the relationship between osteogenic differentiation and IL-1b, IL-6, IL-8, and TNF-a (24,(38)(39)(40)(41). We also investigated the mechanisms of the osteogenesis of HMGB1 on MSCs (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor‐alpha has been documented to regulate bone remodeling by suppressing osteogenesis and activating osteoclastogenesis . Quite a few signaling pathways are involved in mediating the effects of TNFα on osteogenesis as reported . Among them, SMURF1 seems particularly notable because SMURF1 itself is a well‐known negative regulator of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Quite a few signaling pathways are involved in mediating the effects of TNFα on osteogenesis as reported. 6,8,9,[26][27][28]33,34 Among them, SMURF1 seems particularly notable because SMURF1 itself is a well-known negative regulator of bone formation. Osteoblast-specific Smurf1 transgenic mice showed significantly less bone formation.…”
Section: Discussionmentioning
confidence: 99%